'Nested' participation in hierarchical societies? Lessons for social- ecological research and management. (1st October 2010) - Glaser, Marion; Radjawali, Irendra; Ferse, Sebastian; Glaeser, Bernhard
In the shift from community-based ecosystem management to co-management by the government and user groups, the participation of local resource users has remained important. In research, participatory approaches aim to enable local communities to contribute to sustainability knowledge. However, the outcomes of participatory practice have been particularly meagre in hierarchical contexts. The article links the difficulties of participatory practice to the hierarchical features of Indonesian society and examines a recently conducted participatory analysis of the social-ecological dynamics surrounding marine resource management in an Indonesian coral archipelago. We discuss the options and limitations encountered in this distinctly hierarchical society and suggest an approach for designing nested participation in this and similarly hierarchical socio-cultural settings. A visual tool is suggested which particularly supports the participation of ecosystem users in the lower ranks of social hierarchies in the search for more sustainable social-ecological futures.